A Convenient Approach to Luminescent Cyclometalated Platinum(II) Complexes with Organometallic π‐Bonded Benzenedithiolate. Issue 34 (28th August 2018) - Sesolis, Hugo; Gontard, Geoffrey; Jutand, Anny; Gullo, Maria Pia; Bandini, Elisa; Barbieri, Andrea; Amouri, Hani
Abstract : A family of neutral cyclometalated platinum(II) complexes [(C ^ N)Pt(η‐S ^ S)] with π‐bonded benzenedithiolate {(η‐S ^ S) = Cp*Ru(C6 H4 S2 )} and various cyclometalated ligands, {(C ^ N) = 2‐phenylpyridine (ppy), (2 ); 2, 4‐difluorophenylpyridine (F2ppy) (3 ), benzo[ h ]quinoline (bzq) (4 ); dibenzo[ f, h ]quinoline (dbzq) (5 )} were prepared and fully characterized. For comparison purposes the related bipyridine platinum(II) complex [(bpy)Pt(η‐S ^ S)][OTf] (6 ) was also prepared. The electrochemistry behavior of these complexes was investigated and shows the enhanced stability of these compounds toward oxidation due to the presence of Cp*Ru moiety which is now π‐bonded to the benzenedithiolato group. Moreover, several complexes were identified by single‐crystal X‐ray molecular structures. To the best of our knowledge, these are the first structures to be reported for cyclometalated platinum complexes with a π‐bonded benzenedithiolate (bdt) ligand. All of the complexes are luminescent in fluid solution at room temperature and in glassy solution at 77 K; their emission properties can be tuned through ligand variation. Abstract : A convenient synthetic procedure is described for the preparation of cyclometalated platinum(II) complexes [(C ^ N)Pt(η‐S ^ S)] (2 –5 ) from π‐bonded benzenedithiolate {η‐S ^ S = [Cp*Ru(η‐C6 H4 S2 )] – } (1 ). The molecular structures of2, 3, and5 were ascertained by X‐ray diffractions study. Their electrochemical and photophysical properties are reported.